FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PERUSAHAAN SEKTOR CONSUMER NON-CYLICALS YANG GO PUBLIC DI INDONESIA - Fanny Magdalena; Wijaya, Henryanto; Vincent Winaldo; Karen Widjaja; Agus Wahyono (Jurnal Liabilitas, 2025)
The aim of this research is to analyze the influence of capital structure, firm size and managerial ownership with liquidity as a moderating variable on the Firm Value of consumer non-cylicals companies listed on the Indonesia Stock Exchange (IDX). The sample selection used the purposive sampling method and the population for this study was the 2020-2022 period using 96 data consisting of 32 consumer non-cylicals company samples. The research design used in this study is a descriptive research design. This descriptive research was conducted to understand the existence of one or more variables, by not comparing the variables themselves and looking for a relationship with other variables. In this study, the data processing used the Microsoft Excel 2010 program and the data analysis process used Eviews version 10. This study used a random sample selection technique, namely purposive sampling. This activity was carried out from March to July 2024.